Preparation and performance of tannin–glyoxal–urea resin-bonded grinding wheel loaded with sio2 reinforcing particles - Zhang, Jun; Liu, Bowen; Zhou, Yunxia; Essawy, Hisham; Li, Jinxin; Chen, Qian; Zhou, Xiaojian; Du, Guanben (Maderas. Ciencia y Tecnología, 2021)
In this study, an easily prepared bio-based abrasive grinding wheel based on tannin–glyoxal–urea (TGU)thermosetting matrix is presented.The synthesised resin was prepared via co-polycondensation reaction of glyoxal and ureawith condensed tannin, which is a forest-derived product. Fourier transform infrared spectroscopy and electrospray ionisation mass spectrometry results confirmed that urea and glyoxal react well under acidic conditions and that –(OH)CH–NH–group is primarily involved in TGU cross-linking. Differential scanning calorimetry, thermomechanical analysis and thermogravimetric analysis investigations showed that the preparation of TGU resin is easier compared to commercial phenol–formaldehyde (PF) resin; moreover, TGU resin has a more robust chemical network structure, which contributes efficiently to heat resistance and improved mechanical properties. This observation is supported by Brinell hardness, compression resistance and grinding testing; these showed that the new grinding wheel acquired higher hardness, superior resistance against compression and stronger abrasion resistance compared with a PF-based grinding wheel prepared in the laboratory. Moreover, few holes and no cracks were found in the new grinding wheel.